2018
DOI: 10.1038/s41418-017-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of functional haploid spermatids from human germline stem cells by three-dimensional-induced system

Abstract: Generation of functional spermatids from human spermatogonial stem cells (SSCs) in vitro is of utmost importance for uncovering mechanisms underlying human germ cell development and treating infertility. Here we report a three-dimensional-induced (3D-I) system by which human SSCs were efficiently differentiated into functional haploid spermatids. Human SSCs were isolated and identified phenotypically. Meiotic chromatin spreads and DNA content assays revealed that spermatocytes and haploid cells were effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…Besides FSH addition in both media at a concentration of 5 UI/L, in one medium (M1) some molecules known to play a role in GC survival and differentiation were added, like hCG, which stimulates the production of testosterone, known as a differentiation and survival factor for GC ( Sharpe, 1987 ). Moreover, M1 was also supplemented with retinoic acid (RA), which has been exploited in culture of human adult tissue with achievement of meiosis ( Yang et al, 2014 ; Perrard et al, 2016 ; Sun et al, 2018 ). However, while addition of RA to the culture media did not allow GC differentiation in our previous work despite SCs maturation ( de Michele et al, 2017a ), GC differentiation was obtained in this work in M2 in the absence of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides FSH addition in both media at a concentration of 5 UI/L, in one medium (M1) some molecules known to play a role in GC survival and differentiation were added, like hCG, which stimulates the production of testosterone, known as a differentiation and survival factor for GC ( Sharpe, 1987 ). Moreover, M1 was also supplemented with retinoic acid (RA), which has been exploited in culture of human adult tissue with achievement of meiosis ( Yang et al, 2014 ; Perrard et al, 2016 ; Sun et al, 2018 ). However, while addition of RA to the culture media did not allow GC differentiation in our previous work despite SCs maturation ( de Michele et al, 2017a ), GC differentiation was obtained in this work in M2 in the absence of RA.…”
Section: Discussionmentioning
confidence: 99%
“…It is however worth noting that spermatozoa-like cells were obtained after culture in chitosan bioreactors of seminiferous tubules retrieved from transsexual men which had impaired spermatogenesis leaving spermatogonia as residual germ cells in the tissue after hormonal therapy ( Perrard et al, 2016 ). More recently, Sun et al, reported the differentiation of SSCs retrieved from azoospermic adult patients and cultured in a Matrigel system up to haploid cells able to fecundate mouse oocytes ( Sun et al, 2018 ). All other attempts to in vitro differentiate human germ cells (GCs) exploited mature testicular tissue and only allowed the achievement of some steps of GC differentiation in organotypic ( Steinberger et al, 1964 ; Tesarik et al, 2000b ; Roulet et al, 2006 ), or 3D ( Lee et al, 2006 , 2007 ; Yang et al, 2014 ) culture.…”
Section: Introductionmentioning
confidence: 99%
“…First, an efficient approach is required to be developed to differentiate SSCLCs into haploid cells. Sun et al reported that only 6.1% of haploid cells were generated from hSSCs derived OA patients by two-dimensional-induced (2D-I) differentiation system, but 17.9% of haploid cells were produced from hSSCs by three-dimensional-induced system (3D-I) [ 48 ]. In our study, we used 2D-I system to differentiate SSCLCs into haploid cells, thus, in the further research, 3D-I system is needed for the differentiation of SSCLCs into haploid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other research groups revealed similar germ cell development using Vero cells to support the differentiation of spermatocytes in vitro [36]. More recently, in vitro generation of human haploid spermatids, able to develop into embryos after ROSI in murine oocytes, were obtained from SSCs of adult patients with cryptorchidism [37] and obstructive azoospermia [38].…”
Section: Perspectives and Challenges Of Fertility Restoration Strategiesmentioning
confidence: 95%